Current state of plant conservation translocations across Europe: motivations, challenges and outcomes - Sandrine Godefroid; Sam Lacquaye; Andreas Ensslin; Sarah Dalrymple; Thomas Abeli; Hannah Branwood; Inmaculada Ferrando Pardo; P. Pablo Ferrer Gallego; Elke Zippel; Luísa Gouveia; Carlos Alberto Lobo; Francisco Fernandes; et al. (Biodiversity and Conservation, 2025)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Niche breadth of Amazonian trees increases with niche optimum across broad edaphic gradients - Jason Vleminckx; Oscar Valverde Barrantes; Claire Fortunel; C. E. Timothy Paine; David Bauman; Julien Engel; Pascal Petronelli; Nállarett Dávila; Marcos Rios; Elvis Harry Valderrama Sandoval; Italo Mesones; Elodie Allié; et al. (Ecology, 2023)
Understanding how biotic interactions and environmental filtering mediated by soil properties shape plant community assembly is a major challenge in ecology, especially when studying complex and hyperdiverse ecosystems like tropical forests. To shed light on the influence of both factors, we examined how the edaphic optimum of species (their niche position) related to their edaphic range (their niche breadth) along different environmental gradients and how this translates into functional strategies. Here we tested four scenarios describing the shape of the niche breadth—niche position relationship, including one neutral scenario and three scenarios proposing different relative influences of abiotic and biotic factors on community assembly along a soil resource gradient. To do so, we used soil concentration data for five key nutrients (N, P, Ca, Mg, and K), along with accurate measurements of 14 leaf, stem, and root traits for 246 tree species inventoried in 101 plots located across Eastern (French Guiana) and Western (Peru) Amazonia. We found that species niche breadth increased linearly with species niche position along each soil nutrient gradient. This increase was associated with more resource acquisitive traits in the leaves and the roots for soil N, Ca, Mg, and K concentration, while it was negatively associated with wood density for soil P concentration. These observations agreed with one of our hypothetical scenarios in which species with resource conservation traits are confined to the most nutrient‐depleted soils (abiotic filter), but they are outperformed by faster‐growing species in more fertile conditions (biotic filter). Our results refine and strengthen support for niche theories of species assembly while providing an integrated approach to improving forest management policies.

The offshore renewables industry may be better served by new bespoke design guidelines than by automatic adoption of recommended practices developed for oil and gas infrastructure: A recommendation illustrated by subsea cable design - Terry Griffiths; Scott Draper; Liang Cheng; Hongwei An; Marie-Lise Schläppy; Antonino Fogliani; David White; Stuart Noble; Daniel Coles; Fraser Johnson; Bryan Thurstan; Yunfei Teng (Frontiers in Marine Science, 2023)
Introduction There is an emerging need for the offshore renewable industry to have their own bespoke design guidelines because the associated projects and offshore facilities differ in fundamental ways to oil and gas facilities. Offshore renewable energy (ORE) facilities have already surpassed the numbers of installed facilities in the oil and gas industry by an order of magnitude and demand is forecast to continue growing exponentially. In addition ORE facilities often have different response characteristics and limit states or failure modes as well as profoundly different risk and consequence profiles given they are generally uncrewed and do not contain explosive hydrocarbon fluids which might be released into the environment. Therefore, the purpose of this paper is to advocate for licensing bodies and regulators (such as the various national PEL 114 committees) to challenge the process of automatic adoption of oil and gas design processes, while pushing for offshore renewables to be treated differently, when appropriate, with more relevant and applicable guidance. Methods To support this argument we present new bespoke design guidance developed for subsea cables based on specific modes of cable behaviour, which often differ from pipelines. We also show worked examples from recent project experience. The results from on-bottom stability analyses of a set of cables are compared between conventional oil and gas guidance following DNV-RP-F109 versus the stability using cable-optimised approaches. Results The outcomes from the ‘conventional’ oil and gas results are not simply biased compared to cable-optimised design methods, with a trend of being either conservative or unconservative. Instead, the results of the two methods are very poorly correlated. This shows that the oil and gas approach isn't simply biased when applied to cables, but is instead unreliable because it doesn't capture the underlying failure conditions. These analytical comparisons are supported by field observation - the ocean doesn't lie, and makes short work of any anthropogenic structures which are designed with inadequate appreciation of the real world conditions. Discussion To support the rapid growth of ORE, we should therefore actively pursue opportunities to rewrite the design rules and standards, so that they better support the specific requirements of ORE infrastructure, rather than legacy oil and gas structures. With more appropriate design practices, we can accelerate the roll out of ORE to meet net zero, and mitigate the climate crisis.

Impact of climate changes in the suitable areas for Coffea arabica L. production in Mozambique: Agroforestry as an alternative management system to strengthen crop sustainability - Crimildo T. Cassamo; David Draper; Maria M. Romeiras; Isabel Marques; Rogério Chiulele; Marisa Rodrigues; Marc Stalmans; Fábio L. Partelli; Ana Ribeiro-Barros; José C. Ramalho (Agriculture, Ecosystems & Environment, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

International consensus principles for ethical wildlife control - Sara Dubois; Nicole Fenwick; Erin A. Ryan; Liv Baker; Sandra E. Baker; Ngaio J. Beausoleil; Scott Carter; Barbara Cartwright; Federico Costa; Chris Draper; John Griffin; Adam Grogan; et al. (Conservation Biology, 2017)
Human–wildlife conflicts are commonly addressed by excluding, relocating, or lethally controlling animals with the goal of preserving public health and safety, protecting property, or conserving other valued wildlife. However, declining wildlife populations, a lack of efficacy of control methods in achieving desired outcomes, and changes in how people value animals have triggered widespread acknowledgment of the need for ethical and evidence‐based approaches to managing such conflicts. We explored international perspectives on and experiences with human–wildlife conflicts to develop principles for ethical wildlife control. A diverse panel of 20 experts convened at a 2‐day workshop and developed the principles through a facilitated engagement process and discussion. They determined that efforts to control wildlife should begin wherever possible by altering the human practices that cause human–wildlife conflict and by developing a culture of coexistence; be justified by evidence that significant harms are being caused to people, property, livelihoods, ecosystems, and/or other animals; have measurable outcome‐based objectives that are clear, achievable, monitored, and adaptive; predictably minimize animal welfare harms to the fewest number of animals; be informed by community values as well as scientific, technical, and practical information; be integrated into plans for systematic long‐term management; and be based on the specifics of the situation rather than negative labels (pest, overabundant) applied to the target species. We recommend that these principles guide development of international, national, and local standards and control decisions and implementation.

The road to 2020 targets and the learnings from the emblematic South American plant genus Nassauvia (Asteraceae) - Mariana A. Grossi; David Draper; María José Apodaca; Maira S. Vitali; Luciano Pataro; Liliana Katinas; Juan Carlos Moreno Saiz (Biodiversity and Conservation, 2017)

Validity of the Polar V800 heart rate monitor to measure RR intervals at rest - David Giles; Nick Draper; William Neil (European Journal of Applied Physiology, 2016)

Acquiring baseline information for successful plant translocations when there is no time to lose: the case of the neglected Critically Endangered Narcissus cavanillesii (Amaryllidaceae) - David Draper Munt; Isabel Marques; José M. Iriondo (Plant Ecology, 2016)

Strong postzygotic isolation prevents introgression between two hybridizing Neotropical orchids, Epidendrum denticulatum and E. fulgens - Fábio Pinheiro; Poliana Cardoso-Gustavson; Rogério Mamoru Suzuki; Monique Cristine R. Abrão; Leonardo R. S. Guimarães; David Draper; Ana Paula Moraes (Evolutionary Ecology, 2015)

Seed image analysis and taxonomy of Diplotaxis DC. (Brassicaceae, Brassiceae) - Oscar Grillo; David Draper; Gianfranco Venora; Juan Bautista Martínez-Laborde (Systematics and Biodiversity, 2012)

Quantifying garnet-melt trace element partitioning using lattice-strain theory: new crystal-chemical and thermodynamic constraints - Wim van Westrenen; David S. Draper (Contributions to Mineralogy and Petrology, 2007)

Quantifying garnet-melt trace element partitioning using lattice-strain theory: assessment of statistically significant controls and a new predictive model - David S. Draper; Wim van Westrenen (Contributions to Mineralogy and Petrology, 2007)

Ecology matters: Atlantic–Mediterranean disjunction in the sand‐dune shrub Armeria pungens (Plumbaginaceae) - ROSALÍA PIÑEIRO; JAVIER FUERTES AGUILAR; DAVID DRAPER MUNT; GONZALO NIETO FELINER (Molecular Ecology, 2007)
Inferring the evolutionary history of Mediterranean plant lineages from current genetic, distributional and taxonomic patterns is complex because of a number of palaeoclimatic and geological interconnected factors together with landscape heterogeneity and human influence. Therefore, choosing spatially simplified systems as study groups is a suitable approach. An amplified fragment length polymorphism (AFLP) study using two restriction enzyme combinations ( Eco RI/ Mse I and Kpn I/ Mse I) was carried out to estimate the structure of genetic variation throughout the range of Armeria pungens . This species has a West Iberian‐Corso/Sardinian disjunct distribution on coastal sand‐dune ecosystems. Bayesian, amova and genetic distance analyses of the AFLP data revealed the same distinguishable genetic groups, which do not match the main geographical disjunction. Corso‐Sardinian populations were found to be genetically closer to southwest Portuguese than to those from the Gulf of Cadiz (the closest geographically). Eastwards long‐distance dispersal is therefore invoked to explain this geographical disjunction. A GIS analysis based on bioclimatic envelope modelling aiming to characterize the current locations of A. pungens found strong similarities between the Portugal and Corsica‐Sardinia sites and less so between these areas and the Gulf of Cadiz. This coincident pattern between AFLP and climatic data suggests that the geographical disjunction is better explained by climatic factors than by the likeliness of a stochastic dispersal event. Such a combined phylogeographical–GIS modelling approach proves to be enlightening in reconstructing the evolutionary history of plant species.

The last lavas erupted during the main phase of the Siberian flood volcanic province: results from experimental petrology - Linda T. Elkins-Tanton; David S. Draper; Carl B. Agee; Jessica Jewell; Andrew Thorpe; P. C. Hess (Contributions to Mineralogy and Petrology, 2006)

Commercial Speech Recognition Technology in the Military Domain: Results of Two Recent Research Efforts - David T. Williamson; Mark H. Draper; Gloria L. Calhoun; Timothy P. Barry (Genetic Resources and Crop Evolution, 2005)

The measurement of plasma catecholamine and lactate thresholds: a comparison of methods - Terry McMorris; John Sproule; Steve Draper; Rob Child; James R. Sexsmith; C. David Forster; John Pattison (European Journal of Applied Physiology, 2000)